Clinical Evaluation of Accommodative Intraocular Lens Implantation in High Myopic Eyes - Kim, Jae Hui (The Korean Ophthalmological Society, 2008)
PURPOSE: To compare the clinical outcome of AT-45 implantation between high myopic eyes and non-high myopic eyes. METHODS: Retrospective, non-randomized, comparative trial. The medical charts of 28 patients with 35 eyes who had phacoemulsification and AT-45 implantation were retrospectively reviewed. 13 eyes of 10 patients were included in the high myopic group (axial length ≥ 26.0 mm) and 22 eyes of 18 patients were included in the non-high myopic group. The clinical data included unilateral best-corrected visual acuity (BCVA) and distance-corrected near visual acuity (DCNVA) at 6-months follow-up after the surgery. The results were compared between the two groups. RESULTS: In the non-high myopic group, 22 eyes (100%) and 19 eyes (86.4%) achieved a BCVA of 20/25 and 20/20 or better respectively. For the high myopic group, the results were 13 eyes (100%) and 12 eyes (92.3%) respectively, at 6 months after the surgery. In the non-high myopic group, 21 (95.4%) and 7 eyes (31.8%) achieved a DCNVA of 20/40 and 20/25 or better. For the high myopic group, the results were 13 (100%) and 4 eyes (30.8%) respectively, at 6 months after the surgery, the differences between the two groups for a BCVA of 20/25 or better and 20/20 or better and a DCNVA 20/40 or better and 20/25 or better were not statistically significant. CONCLUSIONS: Six months clinical outcome of cataract surgery with an AT-45 for the high myopic eyes was satisfactory; it was not significantly different from that of the non-high myopic eyes.